QUALITY OF LIFE AND FEAR OF FALLING AMONG AN AGING POPULATION IN SEMI RURAL, THAILAND - Yodmai, Korravarn; Phummarak, Sipapa; Sirisuth, Jonathan C; Kumar, Ramesh; Somrongthong, Ratana (Journal of Ayub Medical College Abbottabad, 2015)
Background: Thailand is the country where large numbers of old population are living in rural areas. Multiple factors are influencing the health of old people but falling is the biggest cause affecting their quality of life. This study explores the relationship between the quality of life, and fear of fall among aging people in the semi-rural, Thailand. Methods: A cross sectional study was conducted on 394 old aged individuals living inNakornnayokProvince. Participants were selected through simple random method (SRM) from village population list. Old people were interviewed by adapting World Health Organization quality of life instrument-older module (WHOQOL-OLD) to access the quality of life. Multiple logistic regression analysis was applied to identify factors associated with QOL. Results: Above half of respondents during this study were female, married, educated with age 70.45±6.99. Majority of aging had low income and were not enrolled for their health check-up at hospitals on regular basis. Over a half of them suffered from chronic diseases, and one third of them were using instrumental aids such as visual glasses, walker support, wheel chair and hearing aids etc. Majority, (70%) of the participants was living in safe houses but (34%) reported fall at least one time in past year. Mean of fear of fall score (FFS) was calculated (26.97±4.31) and mean of FFS during using public transportation was (9.8756±2.19467). Two third of aging population reported the moderate quality of life (QOL). Conclusions: Study has concluded that the QOL in aging people is related with household safety and confidence to use public transportation. Keywords: Quality of Life, Fear of Fall, Aging and rural population.